PRODUKSI BIOGAS DARI LIMBAH KOTORAN SAPI DENGAN DIGESTER FIXED DRUM - Irnanda Pratiwi; Rosmalinda Permatasari; Ozkar Firdausi Homza (Politeknik Negeri Sriwijaya, 2019)
Biogas is a gas which produced by anaerobic activity or fermentation of organic materials including; human and animal waste, domestic (household) waste, biodegradable waste or any biodegradable organic waste under anaerobic conditions. The main content of biogas are methane and carbon dioxide. Pulau Semambu Village, Inderalaya Utara Subdistrict is a village which area of the expansion of the Tanjung Seteko Main Village, Inderalaya District, Ogan Ilir Regency. This area has a population of 1055 people / 537 households. In accordance with its geographical location, Pulau Semambu Village has sufficient natural resources to support the success of rural communities to improve their standard of living by utilizing land suitable for agriculture, livestock and plantations. In this case, for livestock cattle manure, its utilization have not achieve an optimal condition.The Community Partnership Program aims to produce supply technology and use a biogas fixed drum digester / reactor capacity of 600 liters for household purposes, especially in Pulau Semambu Village, Kec. Inderalaya Utara, Kab. Ogan Illir.